Structural properties of carbon composites doped with boron; Вестник Карагандинского университета. Серия Физика; № 3 (99) - Piliptsov D. G.; Rudenkov A. S.; Rogachev A. V. Aleksandr Vladimirovich; Tszyan Syao Khun; Kulesh E. A.; Surzhikov A. P. Anatoly Petrovich; Luchnikov A. P. Aleksandr Petrovich; Frolova O. A. Oksana Aleksandrovna (2020, 2020)
The article considers morphology, chemical and phase composition of composite boro-carbon coatings, received by ion-plasma synthesis, depending on the boron content. Specimens of carbon coating doped with boron were obtained in vacuum unit by combined method coupled with co-deposition of carbon layer from pulse carbon plasma and its doping with boron atom flow. The obtained specimens of composite CC had embedded boron atoms with various concentration (NB), namely, 2.3 at.% were contained in ɑ-С91.2:B2.3, in ɑ-С79.3:B17.4 - 17.4 at.%, in ɑ-С53.3:B43.2 - 43.2 at.%. Carbon structures and carbon clusters graphitization were examined by X-ray photoelectron spectroscopy and Raman spectroscopy. Aiming at chemical interaction between carbon and boron in CC establishment we conducted mathematical processing of XPS for energy states C1s, B1s, O1s of carbon, boron and oxygen atoms. XPS C1s was presented as peaks superposition with centers located at 284.5; 285.5; 283.5 and 288 eV and consequently responsible for Csp2 , Csp3 , C-B and C-О carbon atom interaction. With the growth of NB in boron-doped carbon coating a grain structure is formed, its size and grain orientation regarding the surface of the substrate increase, resulting in a decrease in the coating layer surface roughness.